A TIME-SERIES AND SPATIAL ANALYSIS OF 56 YEARS (1961–2017) OF RAINFALL HISTORICAL DATA FROM MALAYBALAY, BUKIDNON - B. J. Buenaobra (Copernicus Publications, 2021)
This paper focuses on using time series and spatial analysis methods to detect climate change indicators in Malaybalay, Bukidnon. We look at 56 years of historical rainfall data between the years 1961 to 2017 and perform a computational method for data processing to arrive at spatial statistics and provide data visualization. We demonstrate the use of the Augmented Dickey-Fuller test (ADF), where a p-value is tested versus a threshold to reject or accept the null hypothesis for a stationarity test. For the seasonality test, we perform a time-domain signal processing by an autocorrelation function. The time-series analysis shows that for Malaybalay, Bukidnon rainfall data shows ADF statistic of −16.348964, a p-value = 0.000000 with critical values 1%:−3.431, 5%:−2.862, 10%:−2.567. Hence, the significant negative values indicate more likely to reject the null hypothesis. We showed that rainfall does not demonstrate periodicity, is not seasonal, and is non-stationary. This work does not cover those that can be detected and attributed to anthropogenic causes.